ANALISIS KINERJA PADA KANTOR PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) PROVINSI SULAWESI TENGAH - Saida, Abdul Rachman (Katalogis, 2015)
The main problem in this study are: to find out about the  performance At the Office of Intergrated Services Center for Women’s Empowerment and Chlid (P2TP2A) Central Sulawesi Province as well as factor affecting the existing Performance Office of Intergrated Services Center for Women’s Empowerment and Chlid (P2TP2A) Central Sulawesi Province. This is a qualitative descriptive study. The research location is the Office of Intergrated Services Center for Women’s Empowerment and Chlid (P2TP2A) Central Sulawesi Province. Data is collected by observation and interviews, information retrieval is done by purposive many as 8 people. The theory used is the Organizational Performance by Agus Dwiyanto, using Performance indicators namely, Productivity, Quality Service, Responsiveness, Responsibilitas, and Accountability. The results showed that the Performance Analysis on the Intergrated Services Center for Women’s Empowerment and Chlid (P2TP2A) Central Sulawesi Province not to walk up. Almost all factors that exist in supporting the performance of the Intergrated Services Center for Women’s Empowerment and Chlid (P2TP2A) Central Sulawesi Province is not running optimally, especialy against Responsibility and Accountability existing.